2020
DOI: 10.1111/cas.14306
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose‐escalation trial to repurpose propagermanium, an oral CCL2 inhibitor, in patients with breast cancer

Abstract: The formation of premetastatic niches creates a fertile environment for the seeding of disseminated cancer cells in selected secondary organs. This is crucial for the development of metastasis in various malignancies, including breast cancer (BC). We previously reported that the loss of FBXW7 in bone marrow‐derived stromal cells promoted cancer metastasis by increasing the production of the chemokine CCL2, which attracts myeloid‐derived suppressor cells and macrophages to the premetastatic niche. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…In fact, propagermanium, a drug used clinically for the treatment of chronic hepatitis in Japan, inhibits C-C chemokine receptor 2 function and reduces macrophage infiltration and atherosclerosis in Apolipoprotein E (ApoE) knockout mice [30]. This has recently been reported in a phase I dose escalation trial with propagermaium in patients with breast cancer [31] and a phase 2 trial with anti-MCP-1 (carlumab) in patients with idiopatic pulmonary fibrosis [32]. In addition, MLN1202, a specific humanized monoclonal antibody that interacts with CCR2-inhibiting MCP-1 binding, was used in a randomized, double-blind, placebo-controlled study in patients at risk for atherosclerotic cardiovascular disease (2 or more risk factors for atherosclerotic cardiovascular disease and circulating CRP >3 mg/L) [33].…”
Section: Discussionmentioning
confidence: 95%
“…In fact, propagermanium, a drug used clinically for the treatment of chronic hepatitis in Japan, inhibits C-C chemokine receptor 2 function and reduces macrophage infiltration and atherosclerosis in Apolipoprotein E (ApoE) knockout mice [30]. This has recently been reported in a phase I dose escalation trial with propagermaium in patients with breast cancer [31] and a phase 2 trial with anti-MCP-1 (carlumab) in patients with idiopatic pulmonary fibrosis [32]. In addition, MLN1202, a specific humanized monoclonal antibody that interacts with CCR2-inhibiting MCP-1 binding, was used in a randomized, double-blind, placebo-controlled study in patients at risk for atherosclerotic cardiovascular disease (2 or more risk factors for atherosclerotic cardiovascular disease and circulating CRP >3 mg/L) [33].…”
Section: Discussionmentioning
confidence: 95%
“…The axis between TNFα signaling and CCL2 has also been studied, in which TNFα increases the expression of CCL2 in human proximal tubular epithelial cells via activation of MAPK signaling (Ho et al, 2008). A recent clinical trial of an inhibitor of CCL2, namely propagermanium, showed proper safety and efficacy in patients with metastatic breast cancer (Masuda et al, 2020). Taken together, CCL2 is a promising target for inhibiting breast cancer metastasis; however, the role of brazilin in metastasis-related to CCL2 and TNFα signaling needs to be explored further.…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 99%
“…Furthermore, we showed that the administration of a CCL2 inhibitor, PG, blocked the enhancement of metastasis by inhibiting the formation of premetastatic niches in a mouse model . Based on these findings, we conducted a phase I dose‐escalation study of PG administration as an antimetastatic drug for perioperative patients with primary breast cancer and showed that PG could be given safely (UMIN000022494) . In addition, Kikuchi et al demonstrated that PG has antitumor activity due to its effects on promoting natural killer cell maturation for patients with metastatic gastric or oral cancer .…”
Section: Clinical Trials Of Drug Repositioning In Japanmentioning
confidence: 98%